2008
DOI: 10.1111/j.1365-2982.2007.01059.x
|View full text |Cite
|
Sign up to set email alerts
|

5‐HT4 receptor agonists: similar but not the same

Abstract: 5-Hydroxytryptamine 4 (5-HT 4 ) receptors are an interesting target for the management of patients in need of gastrointestinal (GI) promotility treatment. They have proven therapeutic potential to treat patients with GI motility disorders. Lack of selectivity for the 5-HT 4 receptor has limited the clinical success of the agonists used until now. For instance, next to their affinity for 5-HT 4 receptors, both cisapride and tegaserod have appreciable affinity for other receptors, channels or transporters [e.g. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
232
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(240 citation statements)
references
References 116 publications
3
232
0
3
Order By: Relevance
“…Experimental data in healthy controls showed that glucagon, a potent muscle relaxant, reduced abdominal symptoms but gas retention and objective abdominal distension were unaffected [77] . Domperidone has been shown to be ineffective in IBS symptoms [118] whereas the administration of neostigmine, a prokinetic drug, produced gas clearance and improvement of both abdominal symptoms and objective distension [119] . Likewise the 5-HT4 receptor agonist tegaserod has demonstrated potent prokinetic effects on small intestinal and colonic transit in IBS patients with constipation, also reducing the symptoms of bloating [120] .…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental data in healthy controls showed that glucagon, a potent muscle relaxant, reduced abdominal symptoms but gas retention and objective abdominal distension were unaffected [77] . Domperidone has been shown to be ineffective in IBS symptoms [118] whereas the administration of neostigmine, a prokinetic drug, produced gas clearance and improvement of both abdominal symptoms and objective distension [119] . Likewise the 5-HT4 receptor agonist tegaserod has demonstrated potent prokinetic effects on small intestinal and colonic transit in IBS patients with constipation, also reducing the symptoms of bloating [120] .…”
Section: Treatmentmentioning
confidence: 99%
“…For these reasons, its use in clinical practice is very limited. Prucalopride is a highly selective 5-HT4 receptor agonist with strong enterokinetic activity [124,125] and requires lower dose for this therapeutic effect [119] making this drug potentially suitable for bloating patients [126] . Itopride, a dopamine receptors antagonist and acetylcholinesterase inhibitor, has shown conflicting results in patients with functional dyspepsia [127,128] .…”
Section: Treatmentmentioning
confidence: 99%
“…In particolare è stata esplorata la possibilità di favorire il transito intestinale mediante l'azione di procinetici che agiscono come agonisti del recettore serotoninergico 5-HT4. Nel 2009 è stata autorizzata a livello europeo l'immissione in commercio di prucalopride, primo agonista selettivo del recettore 5-HT4 appartenente a una nuova classe di benzofurani, indicato, dietro presentazione di ricetta medica [2], per il trattamento della stipsi cronica idiopatica delle donne dopo il fallimento di altri comuni lassativi [38].…”
Section: Trattamenti Farmacologiciunclassified
“…Approximately 80% of the human body's total 5-HT is located in the enterochromaffin cells in the gut, where it is reported to be involved in intestinal movements via several 5-HT receptor subtypes [3,6]. Based on biochemical and pharmacological criteria, 5-HT receptors are classified into seven main receptor subtypes, five of which are present on enteric neurons, enterochromaffin cells and GI smooth muscles, namely 5-HT1, 5-HT2, 5-HT3, 5-HT4 and 5-HT7 [7,8]. With the exception of the 5-HT3 receptor, a ligand-gated ion channel, all 5-HT receptors are G protein-coupled receptors that activate an intracellular second messenger cascades to produce either excitatory or inhibitory responses [8].…”
Section: Introductionmentioning
confidence: 99%